PENINGKATAN JUMLAH STATUS JANDA DAN DAMPAK PERCERAIAN: (Studi Kasus Desa Sukorejo, Kecamatan Sumber Wringin, Kabupaten Bondowoso) - wakik, wakik; Rofiq, Ainur (Al-Qawaid Research Centre of the Department of Islamic Family Law, 2024)
Divorce is an important aspect of marriage law and falls within the realm of civil law, significantly impacting social structure and individuals. This study examines the increase in the number of widows due to divorce and its implications, focusing on the underlying factors contributing to this phenomenon. The research notes that economic factors, such as the inability to provide adequate support, unemployment, and lack of income, account for about 14% of total divorce cases. Additionally, domestic violence also plays a role as a cause of divorce, although its contribution is relatively small (0.6%). Nevertheless, the trend of domestic violence tends to increase and affects household stability. Ongoing disputes and arguments are dominant factors, contributing 36% and 29% of total divorce cases based on data from the Religious Court. Infidelity is also often a significant cause of divorce. This research is expected to provide deeper insights into the social impacts of divorce and inform policies and support for affected individuals.